2022
DOI: 10.1001/jamanetworkopen.2022.34319
|View full text |Cite
|
Sign up to set email alerts
|

Association of Household Deprivation, Comorbidities, and COVID-19 Hospitalization in Children in Germany, January 2020 to July 2021

Abstract: ImportanceAdults in disadvantaged socioeconomic positions have elevated risks of a severe course of COVID-19, but it is unclear whether this holds true for children.ObjectiveTo investigate whether young people from disadvantaged households have a higher risk of COVID-19 hospitalization and whether differences were associated with comorbidities that predispose children to severe courses.Design, Setting, and ParticipantsThis population-based cohort study included all children and adolescents (aged 0-18 years) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Also, vaccinations were not generally available during the study period for this age group and therefore unlikely to account for these associations. The findings from this study by Dragano et al 2 suggest that there is a cost associated with social disadvantage, even in settings with established social systems.…”
mentioning
confidence: 44%
“…Also, vaccinations were not generally available during the study period for this age group and therefore unlikely to account for these associations. The findings from this study by Dragano et al 2 suggest that there is a cost associated with social disadvantage, even in settings with established social systems.…”
mentioning
confidence: 44%
“…However, relatively few studies examining changes in the incidence rate of pediatric diabetes since the onset of the COVID-19 pandemic have reported the socioeconomic status, race, or ethnicity of the study population. Such information would elucidate whether health disparities in the incidence rates of diabetes and DKA widened during the pandemic …”
Section: Discussionmentioning
confidence: 99%
“…Such information would elucidate whether health disparities in the incidence rates of diabetes and DKA widened during the pandemic. 80 , 81 …”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Socio-economic disparities in healthcare utilization, such as delayed diagnosis, suboptimal management, and higher rates of complications, contribute to the unequal burden of disease in vulnerable populations. [9,10,13] In a recent meta-analysis of 28 studies, Best et al showed that lower socio-economic status was associated with increased risk of short-term and long-term mortality at different ages (neonates, infants and children) of children with CHD. [14] There are national and regional data exploring disparities in outcomes based on race and socio-economic conditions in CHD populations [15,16] [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%